2022
DOI: 10.3390/ani12151965
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility of a Lignocellulose Supplemented Diet and Fecal Quality in Beagle Dogs

Abstract: Lignocellulose (LC) might be used as a substitute fiber source for dogs as a strategy to decrease energy density and enhance gastrointestinal functionality. The objective of the present study was to compare the effects of including different levels of LC on apparent nutrient digestibility and fecal parameters (dry matter (DM), fecal score, and daily fecal output), as well as fecal fatty acid concentrations. Four diets were tested: control diet (no supplementation of LC; LC0), and three control diets diluted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Fecal consistency scores were calculated using a five-point scale: 1 for extremely hard feces; 2 for solid, well-formed, 'optimum' feces; 3 for soft, still-forming feces; 4 for pasty, slushy feces; and 5 for watery diarrhea, in accordance with Moxham [ 43 ], as shown in Figure 1 . The fecal form scoring system devised by Abd El-Wahab et al [ 44 ] involves a four-point scale (where 1 represents an individual fecal mass; 2, strong constrictions at the ‘optimal’ fecal surface; 3, cracks at the fecal surface; and 4, shapelessness), which was used to describe the shape of feces.…”
Section: Methodsmentioning
confidence: 99%
“…Fecal consistency scores were calculated using a five-point scale: 1 for extremely hard feces; 2 for solid, well-formed, 'optimum' feces; 3 for soft, still-forming feces; 4 for pasty, slushy feces; and 5 for watery diarrhea, in accordance with Moxham [ 43 ], as shown in Figure 1 . The fecal form scoring system devised by Abd El-Wahab et al [ 44 ] involves a four-point scale (where 1 represents an individual fecal mass; 2, strong constrictions at the ‘optimal’ fecal surface; 3, cracks at the fecal surface; and 4, shapelessness), which was used to describe the shape of feces.…”
Section: Methodsmentioning
confidence: 99%
“…(VDLUFA) [ 18 ]. The dry matter (DM), crude ash, crude protein, and ether extract were determined as described by Abd El-Wahab et al [ 19 ]. Briefly, to calculate the DM content, the samples were dried for 12 h (103 °C) and weighed before and after.…”
Section: Methodsmentioning
confidence: 99%
“…Ion-exchange chromatography, using the amino acid analyzer LC 3000 (Biotronik, Maintal, Germany), was then used to assess the amino acid content as previously described [ 19 ]. The National Research Council (NRC) [ 17 ] suggested that the ME content of the diets be calculated based on their chemical composition.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical trials provide evidence supporting that linseed mucilage, being abundant in soluble fiber, effectively contributes to the reduction of body weight ( 124 , 125 ). Another possible mechanism responsible for this is the significant decrease in energy intake ( 126 ).…”
Section: Health Benefits Associated With Linseed Mucilagementioning
confidence: 99%